Beyond the Acronym: Intersections of STEAM, Cybernetics, and Leadership Nurturing - Christopher Dignam (Journal of Education in Science, Environment and Health)
The theoretical model presented in this study explores the transformational potential of a digital Community of Practice (dCoP) within higher education, focusing on Science, Technology, Engineering, Art, and Mathematics (STEAM) education. A dCoP serves as a virtual space for educators to exchange knowledge, foster interdisciplinary collaboration, and construct meaning through discourse. Through the use of digital artifacts, a dCoP provides tangible exemplars for intersecting abstract concepts to real-world applications, thus strengthening educational experiences and outcomes. This study emphasizes the cognitive, social, and emotional skills developed through STEAM education, projecting future career growth for learners in these areas. Establishing a dCoP for teachers in higher education facilitates the transfer of interdisciplinary and transdisciplinary skills to students, supporting STEAM learning and future career opportunities. Additionally, this study employs portraiture and autoethnography methodology for storytelling and cybernetic learning. The incorporation of a cybernetic mindset, presented through a theoretical Cybernetic Three-Realm Model, enriches a dCoP by addressing (1) a Canvas for Scholarship of Teaching and Learning (SoTL), (2) an Artist’s Palette for Authentic Artifacts, and (3) The Paints of Modalities for Learning. This theoretical construct affords a tangible framework for fostering STEAM skills and nurturing leadership development for pervasive learning within higher education dCoPs.